A comparison between the effects of strength versus power-focused post-activation potentiation for sprint performance in physically fit young adult males - Madjus, Trent Genesis N.
Post-activation potentiation or PAP has been utilized as part of the warm-up protocol to enhance subsequent athletic performance. Previous studies on PAP have shown improvements in athletic performance following a conditioning activity of resistance exercise or plyometrics. However, there is no consensus yet regarding which type of PAP should be used before a main activity. The objective of this study was to determine and compare the effects of strength-focused and power-focused PAP before short sprint performance. Nine (9) physically fit young adult males with a mean age of 24.1 ± 1.7 years participated in this study. Only five (5) participants were able to complete the testing process. Four (4) non-consecutive days were allotted for the testing process, with a minimum of 48 hours between testing days given for complete recovery. The participants had their 20-m baseline sprint time measured on a track oval using timing gates. The participants then had their one repetition maximum on the barbell half squat exercise measured. They were then divided into 2 groups, which determined the PAP intervention they would perform first. After each intervention, participants were tasked to perform a 20-m maximal effort sprint at 4- and 8-minutes post-intervention. The results gathered in this study showed no significant difference between the pre- and post-test scores of the participants who performed the interventions. This implied that neither PAP intervention was able to induce a potentiation that would significantly affect sprint performance for this set of participants. This study showed no conclusive evidence to support the claim that PAP improves athletic performance, especially in recreational runners with weight training experience. The findings of this study affirm prerequisites to induce PAP itself, such as an individual’s fitness level, intensity, and movement specificity. Considering these factors might help in future research regarding PAP.